Agronomic performance of cowpea genotypes in southwestern Brazilian Amazon - Marinho, José Tadeu de Souza; Lessa, Lauro Saraiva; Costa, Charles Rodrigue da (Pesquisa Agropecuaria Brasileira, 2021)
The objective of this work was to evaluate the agronomic performance of cowpea (Vigna unguiculata) genotypes over three crop years, in the ecosystem of Rio Branco, in the state of Acre, Brazil. The experiments were carried out in the 2016, 2017, and 2018 crop seasons, in a randomized complete block design, with four replicates. Eight agronomic traits were evaluated in 14 cowpea genotypes, which included: 12 lines (BDO 1-5-11, BDO 1-5-15, BDO 1-5-19, BDO 1-5-24, PDO 1-5-26, PDO 1-5-4, PDO 1-5-5, PDO 1-5-7, PDO 1-5-8, PDO 1-5-10, PDO 1-5-11, and PDO 1-5-14) and two cultivars (BRS Tumucumaque and BRS Imponente). A significant difference was observed in the genotype x crop year interaction, for most traits. Although there was no statistical difference between genotypes in the studied crop years, dry seed productivity was higher than the national average. All cowpea lines and cultivars from the genetic breeding program show equivalent and favorable agronomic performances in the environmental conditions of Rio Branco. Therefore, these genotypes can be selected for incorporation into the production system of Rio Branco.